PRESCHOOL EDUCATIONAL ORGANIZATION FORMATION OF CHILDREN'S ADAPTATION SKILLS (European Journal of Interdisciplinary Research and Development, 2023)
This article covers the adaptation of children to preschool education in the organization and the formation of skills.